Burden of hypertension and associated risk factors among the Nicobarese tribe of Car Nicobar Island, India - Thiruvengadam, Kannan; Muruganandam, Nagarajan; Sivanandan, Nimisha; Parvez, Rehnuma (International Journal Of Community Medicine And Public Health, 2024)
Background: Hypertension, a significant risk factor for various non-communicable diseases, poses a preventable threat to mortality and disease burden. However, there remains a lack of data on hypertension within Indian tribes, particularly those residing in impoverished areas. Determining the prevalence of hypertension and identifying associated risk factors among the Nicobarese tribes. A cross-sectional survey was conducted, involving 2600 tribal individuals aged 18 years and above from ten randomly selected villages on Car Nicobar Island. Methods: A structured questionnaire was utilized to gather data on blood pressure (BP), anthropometric measurements, and detailed participant characteristics. Prevalence of hypertension was determined and analyzed in relation to various identified risk factors using chi-square, Karl Pearson coefficient of correlation, and generalized linear models. Prevalence ratio and adjusted risk ratio calculated, along with their corresponding confidence intervals. Results: Prevalence of hypertension was 57.9%. Several factors, including age, male gender, illiteracy, diabetes, smoking, alcohol consumption, and higher body mass index (BMI), were significantly associated with hypertension. Systolic and diastolic BP levels increased significantly with age, socio-economic scores, BMI, and weight. Conclusions: The prevalence of hypertension among the Nicobarese tribes is significantly higher compared to the general population. Adapting preventive strategies based on an understanding of the tribe's specific culture and lifestyle is important for controlling hypertension. However, it is also crucial to consider genetic and environmental influences that may contribute to the high prevalence of hypertension in this tribe.